Change in the geometry of positive- and negative-powered soft contact lenses during wear - Kaluzny, Bartlomiej J. (PLoS One, 2020)
Contact lens wear causes mutual interactions between the ocular surface and the lens, which may affect comfort as well as vision. The aim of this study was to examine deformations in modern positive- and negative-powered silicone hydrogel soft contact lenses (SiH SCLs) after 7 days of continuous wear. This pre-post interventional study included 64 eyes: 42 eyes with myopia of -3.00 D and 22 eyes with hyperopia of +3.00 D. All patients underwent general ophthalmic examination, corneal topography/tomography, total corneal and epithelial thickness mapping, and specular microscopy before and after the wearing period. SiH SCLs made of senofilcon A were worn continuously for 7 days on all eligible eyes. The geometry of the new and used lenses was measured 3 to 6 minutes after removal in two perpendicular planes using a custom-made swept source optical coherence tomography (SS-OCT) system for in vitro measurements. The anterior and posterior radii of curvature decreased in -3.00 D lenses in two perpendicular planes. This effect correlated significantly with average keratometry of the cornea. Sagittal lens height was lower in +3.00 D lens after wear, which correlated moderately with the corneal sagittal height. A significant decrease in central corneal epithelial thickness was observed after wearing +3.0 D lenses. In conclusion, SiH SCLs made of senofilcon A undergo minor deformations after 7-day continuous wear. Geometry modifications are different for -3.00 D and +3.00 D lenses, and they imitate the shape of the anterior eye surface. These geometric changes are accompanied by a decrease in the central thickness of corneal epithelium after +3.00 D lens wear.